2018
DOI: 10.1007/s00436-018-5922-7
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected case of a Japanese wild boar (Sus scrofa leucomystax) infected with the giant thorny-headed worm (Macracanthorhynchus hirudinaceus) on the mainland of Japan (Honshu)

Abstract: The giant thorny-headed worm Macracanthorhynchus hirudinaceus is a zoonotic acanthocephalan species with a worldwide distribution. Its natural definitive hosts are primarily pigs and wild boars (Sus scrofa), and scarabaeid beetles serve as the intermediate host. To date, there has only been one record of this acanthocephalan in Japan: a Ryukyu wild boar (Sus scrofa riukiuanus) hunted in 1973 on Amami Island, faraway from the Japanese mainland. The present study reports the second case of this acanthocephalan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Macracanthorhynchus hirudinaceus eggs are very resistant in the environment and remain infectious for up to 3 years, tolerating both drought and below-zero temperatures ( 32 ). Currently, the reduced number of reports of human cases is probably a consequence of the low endemicity of the parasite due to the changes in pig farming and improved health education ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macracanthorhynchus hirudinaceus eggs are very resistant in the environment and remain infectious for up to 3 years, tolerating both drought and below-zero temperatures ( 32 ). Currently, the reduced number of reports of human cases is probably a consequence of the low endemicity of the parasite due to the changes in pig farming and improved health education ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The amplified region corresponded to the approximate middle region of the small subunit ribosomal ribonucleic acid gene, which is ∼1800 nt in length (see García-Varela et al, 2021). Comparative sequence analysis revealed that this sequence differs by 1 nt (0.21%), consisting in a nucleotide substitution, from the three M. hirudinaceus sequences obtained by Kamimura et al (2018) from specimens infecting wild boar in Japan (LC350000-2), the only 18S rDNA sequences for this species currently available in GenBank. The other species of this genus for which genetic data are available, M. ingens, is represented by two 18S rDNA sequences in GenBank.…”
Section: Molecular Resultsmentioning
confidence: 98%
“…The European sequences were more similar to each other compared to the Japanese sequence displaying heterogeneity among the different geographical populations. Only two reports of M. hirudinaceus occurrence are reported in Japan and are yet to be established whether this species is accidentally introduced or has endemic status (Kamimura et al 2018). But the clustering of Japanese isolate separately from the European population shows that independent factors are operative at different geographical areas affecting the genetic structure of the species.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from six collected worms was extracted using G-spin™ Total DNA Extraction kit (iNtRON Biotechnology, Korea) according to the manufacturer's instructions. PCR amplification of the mitochondrial cytochrome c oxidase subunit 1 gene (cox1) was performed using one set of primers, Acanth_Cox1-F1 (5′-TTT GGA GGG GTT TGA TGG GT-3′) and Acanth_Cox1-R4 (5′-CCC CAG ACA TTC TTC TCT CCA-3′), and the same conditions previously described (Kamimura et al 2018). PCR products were purified using Nucleospin Gel and PCR Clean Up (Macherey-Nagel GmbH & Co. KG, Düren, Germany) and sent to an external sequencing service (Eurofins Genomics, Ebersberg, Germany).…”
Section: Biomolecular Analysismentioning
confidence: 99%
See 1 more Smart Citation